Consequences of the 1980-2000 violence among students of the REPARED Scholarship: A qualitative study of the psychosocial effects - Gabriel Sinche, Nancy (2020)
The purpose of this article is to gather information and describe the psychological and social consequences in a group of students of the REPARED Scholarship. Through a qualitative methodology, six students from higher education institutions in Lima were interviewed, for the years 2012, 2013 and 2014. The information obtained shows that the psychological consequences of political violence remained in the life of the students, leading to mood disorders represented by depression, anxiety, suffering, fear and distrust towards others, with repercussions on their physical health. As for the social consequences, problems to socialize, orphanhood, family disintegration, stigmatization, discrimination, and economic difficulties were identified.